Early aseptic loosening of a press-fit radial head prosthesis – A case series of 6 patients. Issue 4 (April 2023) - Corbaz, J; Barimani, B; Vauclair, F
Objective: Radial head arthroplasty (RHA) is the principal treatment option for comminuted radial head (RH) fractures. Here, we present six cases of failed RHA using a modular monopolar press-fit RHA that was subsequently withdrawn from the market because it was associated with a high incidence of loosening. Methods: We retrospectively collected data from six patients who had received Radial Head Prothesis System TM at our centre between July 2015 and June 2016. The average follow-up was 40 months. Results: Aseptic loosening of the stem affected five (83%) of the six RHA. Four of these were symptomatic and RHA removal was performed. For these patients, the pain subsided and their elbow range of motion (ROM) improved. Conclusion: While the ideal design for an RHA is still debatable, RHA is an efficient treatment option that restores elbow stability and function after a comminuted RH fracture. Importantly, removal of the prosthesis is an effective remedy following RHA associated elbow pain and decreased ROM.